The course of the disease in tuberculosis patients who recieve methadone substitution therapy - Yasinskyi, R. M.; Cherukuri, R.; Ясінський, Роман Миколайович (Запорізький державний медичний університет, 2018)
Introduction: There is an increased incidence of tuberculosis (TB) and human immune deficiency virus infection (HIV) in drug users. According to research in USA and Europe, substitution therapy has increased adherence to etiotropic specific therapy but there is very little information on the impact of methadone maintenance therapy (MMT) on the outcome of TB treatment. Aim: To determine the effects of methadone maintenance therapy on the course of chemo drug resistant TB. Materials and methods: We analyzed 22 case histories of chemo drug resistant TB patients who are drug users. We divided them into two groups. Group 1 consisted of 10 patients who received MMT. Group 2 consisted of 12 patients without MMT. These groups were compared based on parameters of age, gender, HIV status and types of resistance. The treatment outcomes were determined by treatment adherence, mortality, treatment failure, and positive dynamics. The groups were compared using non-parametric statistics (one-tailed Fisher exact).
Keywords: тези доповідей